Persebaran Indeks Massa Tubuh Mahasiswi Tahun Ke-4 Pendidikan Dokter Universitas Lampung - Rio Sanjaya; Anggi Setiorini; Eka Putri Rahmadhani; Waluyo Rudiyanto (Medula, 2026)
Students in early adulthood are vulnerable to lifestyle changes associated with academic demands and the university environment, which may ultimately affect their nutritional status. One commonly used indicator for assessing nutritional status is Body Mass Index (BMI). Changes in dietary patterns, irregular physical activity, and suboptimal sleep quality may increase the risk of nutritional imbalance among students. This study aimed to determine the distribution of Body Mass Index among female medical students of the 2022 cohort at the Faculty of Medicine, University of Lampung. This study employed an observational design with a cross-sectional approach and involved 175 female students as research participants. Data were collected through anthropometric measurements, including body weight on a digital scale and height on a microtoise. BMI values were calculated as body weight divided by height squared and then classified according to standard anthropometric criteria. The results showed that the majority of respondents had normal nutritional status based on BMI, with 123 students (70.3%). Meanwhile, 23 students (13.1%) were classified as underweight, 11 students (6.3%) as overweight, and 18 students (10.3%) as obese. These findings are consistent with previous studies reporting a predominance of normal BMI among student populations. However, the presence of nearly one-third of respondents with abnormal BMI indicates the influence of lifestyle-related factors, such as dietary habits, physical activity levels, sleep quality, and daily behaviors. Therefore, promotive and preventive efforts through nutritional education and the adoption of healthy lifestyle practices are necessary to maintain optimal nutritional status among students.